2020
DOI: 10.29333/ejosdr/7596
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Energy Audit in Diesel Engine Fuelled with Biodiesel Blends: Review and Analysis

Abstract: Number of experiments have been performed on various performance and emission characteristics, effect of biodiesel blends on lubricity and input and output energy distribution in diesel engine fuelled with biodiesel blends. It is also reviewed that energy audit is used in buildings, plants, process and equipments and energy audit method was developed for fishing vessels based on similar systems for land based industries. In land based businesses, industries and households, energy audits are presently used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…It is concluded that the following performance and emission characteristics of the diesel engine have been chosen as important parameters to evaluate diesel engine fuelled with diesel and biodiesel blends by energy audit at the primary level (Mohite & Maji, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that the following performance and emission characteristics of the diesel engine have been chosen as important parameters to evaluate diesel engine fuelled with diesel and biodiesel blends by energy audit at the primary level (Mohite & Maji, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Brake Specific Energy Consumption, Heat Flow Analysis, Friction Power, Smoke Emission have been found to have more influence and effect than other parameters. During primary stage of energy audit, Brake Specific Energy Consumption, Heat Flow Analysis, Friction Power, Smoke Emission have been preferred to compare results (Mohite & Maji, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that a biofuels certification method is needed in the biofuels industry to authenticate biodiesel and its blends for use in diesel engines [1]. A standard energy audit method is required to evaluate the feasibility of biodiesel blend as fuel and also harmonise the research of biodiesel as fuel [2].…”
Section: Introductionmentioning
confidence: 99%